State-of-the-art of surface integrity in machining of metal matrix composites. (August 2019) - Liao, Zhirong; Abdelhafeez, Ali; Li, Haonan; Yang, Yue; Diaz, Oriol Gavalda; Axinte, Dragos
Abstract: Metal matrix composites (MMCs), as advanced substitutes of monolithic metallic materials, are currently getting an increasing trend of research focus as well as industrial applications for demanding applications such as aerospace, nuclear and automotive because of their enhanced mechanical properties and relative lightweight. Nevertheless, machining of MMC materials remains a challenging task as a result of their structural heterogeneity which leads to deterioration of the machined surface integrity and rapid tool wear. While most of the research was focused on testing and analytical/numerical investigations of the tool wear, limited work was focused on machined surface integrity of MMCs. This paper presents a detailed literature survey on the conventional and non-conventional machining of metal matrix composites with the primary focus on the aspects related to workpiece surface integrity. The contribution of material mechanical and microstructural properties as well as the material removal mechanism upon the quality of workpiece surfaces/subsurface are discussed along with their influences on the fatigue performance of machined part. Highlights: State of the-art review of machined surface integrity of metal matrix composites (MMCs). Conventional and non-conventional machining of MMCs stating the main influences on surface integrity. Effects of machined surface integrity on the functional performance of MMCs. Comparison of the potential of each machining technique stating the current research trends and the current gaps.